Effectiveness evaluation of hemibody irradiation as palliative treatment of patients with multiple painful bone dissemination - Miszczyk, Leszek; Gaborek, Aleksandra; Wydmański, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2005)
Effectiveness of hemibody irradiation (HBI) of 61 patients with multiple painful bone dissemination treated between 2001-2004 was evaluated. 21 patients had UHBI and 40 LHBI. Pain intensity on an 11-degree scale, pain frequency on a 4-degree scale and the kind of analgesics used were evaluated. Patients were examined on HBI day, 2 weeks later and next, every month. Dependencies between pain before HBI and pain relief 2 and 6 weeks later were checked. Pain 2 and 6 weeks after U and LHBI, and pain relief at that time for breast and prostate patients were compared. Mean pain intensity on HBI day was 6.3 and decreased to 3.0 after 2 weeks. Subsequent values were 4.0, 3.0, 3.0, 4.5, 2.0 and 3.4 six months later. Mean pain frequency on HBI day was 3.1 and did not change significantly (from 2.8 to 3.0). On HBI day 3.4% of patients did not use analgesics, 31% used NSAID, 8.6% tramadol, 10.3% opioids, 10.3% NSAID+tramadol and 36.2% NSAID+opioids, so 46.5% used opioids. A percentage of patients without analgesics increased to 37.5% and a percentage using opioids decreased to 25% 3.5 months later. Dependency between pain before HBI and pain relief 2 weeks later was found. Pain relief 2 and 6 weeks after HBI was higher for breast than for prostate patients. No difference between U and LHBI effectiveness was found. Obtained results allow us to conclude that HBI is an effective and simple treatment modality for patients with multiple painful skeletal dissemination allowing an analgesics intake to be decreased.